케이블TV 지역채널의 저널리즘 행위와 규제에 대한 이해당사자 인식 : 〈KCTV제주방송〉 사례를 중심으로 - 이서현(Seohyeon Lee); 최낙진(Nak-Jin Choi) (언론정보연구, 2024)
종합유선방송사업자(SO)이자 지역채널인 KCTV제주방송은 제주도민과 시청자, 그리고 방송연구자들 사이에서 저널리즘 역할을 잘 수행하는 지역방송국으로 회자되곤 한다. 하지만 이를 뒷받침할 관련 연구나 지표는 부족한 상황이다. 이에 본 연구는 KCTV 내부종사자와 외부관계자인 지상파 방송 종사자, 지역언론 연구자를 대상으로 심층인터뷰를 진행하여 지역방송국으로서 KCTV의 저널리즘 행위에 대해 살펴보았다. 연구결과는 다음과 같다. 우선 타 방송사와 달리 중앙방송에 종속되지 않는, 즉 태생적 특성에 기반한 편성의 자율성과 충분한 방송시간 확보가 지역성 구현의 주요 요인으로 인식되고 있었다. 한편, 케이블 채널에만 부과된 ‘해설·논평 금지’와 같은 규제에 대해 내부종사자들은 ‘구시대적 발상’이자 폐지되어야 할 ‘사문화된 조항’이라 여기고 있었다. 외부관계자들은 케이블TV의 저널리즘 행위가 공공성 구현에 오히려 부정적인 영향을 줄 수 있다고 보면서도, KCTV의 24시간 자체 편성과 광케이블을 활용한 실시간 방송을 지역성 구현을 최적화 할 수 있는 요인으로 받아들이고 있었다. 종합적으로 KCTV가 해설·논평 금지라는 규제와 상대적 공적 지원의 미비에도 불구하고 편성의 자율권과 다양한 시청자 접근권 확대 등 지역민 친화적인 하이퍼로컬 미디어로서의 특성을 보여주고 있음을 확인할 수 있었다. As a comprehensive cable television operator (SO) and local channel, KCTV Jeju Broadcasting is often regarded among Jeju residents, viewers, and broadcasting researchers as a local broadcaster that performs its journalistic role well. However, there is a lack of related research or indicators to support this reputation. Therefore, this study conducted in-depth interviews with internal KCTV employees and external stakeholders, including terrestrial broadcasting employees and local media researchers, to examine KCTV's journalistic activities as a local broadcaster. The results of the study are as follows. First, unlike other broadcasters, the autonomy of programming based on its inherent characteristics and the securing of sufficient broadcasting time were recognized as major factors in realizing locality. Meanwhile, internal employees considered regulations imposed only on cable channels, such as the 'ban on commentary and analysis,' as 'outdated concepts' and 'dead clauses' that should be abolished. External stakeholders acknowledged that the journalistic activities of cable TV could negatively impact the realization of public interest, but they also accepted that KCTV's 24-hour self-programming and real-time broadcasting utilizing fiber optic cables could optimize the realization of locality. Overall, it was confirmed that KCTV, despite regulations such as the ban on commentary and analysis and the relative lack of public support, demonstrates characteristics of a hyperlocal media that is friendly to local residents, such as programming autonomy and expanding various viewer access rights. KCI Citation Count: 0